Trends and gaps in the study of fire effects on plant–animal interactions in Brazilian ecosystems - Ballarin, Caio S. [UNESP]; Mores, Guilherme José [UNESP]; Alcarás de Goés, Guilherme [UNESP]; Fidelis, Alessandra [UNESP]; Cornelissen, Tatiana (Wiley, 2024)
Plant–animal interactions are pervasive in terrestrial ecosystems. They hold relevant ecological information for guiding biodiversity conservation and restoration practices. Despite plant–animal interactions being particularly sensitive to disturbance, the knowledge about how fire, a remarkable driver of changes in ecosystem structure and functioning, affects these relationships is still limited. In this sense, the assessment of how studies investigate the fire effects on plant–animal interactions through a systematic review proves to be relevant to guide future research agenda. In this study, we reviewed studies regarding the effects of fire on plant–animal interactions conducted in Brazil, which hosts many different fire-prone and fire-sensitive ecosystems and harbours several plant and animal species. Supported by an integrative database, we summarized the main goals, methodologies, and taxonomic groups used in studies addressing the effects of fire on plant–animal interactions and pointed out some shortfalls that future research should avoid and gaps that they shall fulfil. In sum, 39 studies published from 1995 to 2022 met our criteria of inclusion in the database. Most of them were conducted in Cerrado and mainly evaluated ant–plant or plant–pollinator interactions. In addition, studies were generally designed with inappropriate experimental approaches that commonly disregard relevant fire attributes that are important drivers of ecosystem structure and functioning. Altogether, our review shows that studies evaluating this topic present a geographic and taxonomic bias, which overlooks particular plant–animal interactions, and that we still have a superficial understanding of fire effects on plant–animal interactions in Brazilian ecosystems.
Keywords: ants; fire-prone ecosystems; fire-sensitive ecosystems; herbivory; pollination